Sustainable Consumption of Vegetables – A Matter of Trust as Well - Nikolaeva, Valeria (Research Papers, 2022)
Sustainable consumption of vegetables presupposes consumers to be informed about the origin, production method and the resulting environmental, social and economic effects. This, in turn, requires traceability, transparency, accountability and trust in the supply chain. The article analyzes possible measures for encouraging sustainable vegetable consumption and mechanisms for building trust, the incentives for their use by the supply chain participants and their applicability in Bulgaria.
Keywords: Production of vegetables; Trust; Sustainable consumption